2012
DOI: 10.1080/10665684.2012.717486
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Inequality in the Stratification of Four-Year College Destinations

Abstract: Rooted in sociological models of educational transitions and tracking, this study examines patterns of stratification in the educational trajectories of low-and high-socioeconomic students.Utilizing longitudinal data from the Educational Longitudinal Study of 2002, this study describes qualitative differences in students' choice sets based on a number of metrics obtained from the Integrated Postsecondary Data System (IPEDS). Additionally, multinomial logistic regression models are used to demonstrate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Thus, it matters where a student goes to college. Yet traditionally under-represented racial minority and lower-income students consistently enroll at less selective colleges than white and higher-income students (Alon and Tienda 2007;Astin and Oseguera 2004;Baker et al 2018;Bastedo and Jaquette 2011;Engberg 2012;Posselt et al 2012), setting up the potential for a reproduction of the existing income gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it matters where a student goes to college. Yet traditionally under-represented racial minority and lower-income students consistently enroll at less selective colleges than white and higher-income students (Alon and Tienda 2007;Astin and Oseguera 2004;Baker et al 2018;Bastedo and Jaquette 2011;Engberg 2012;Posselt et al 2012), setting up the potential for a reproduction of the existing income gaps.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these general enrollment gaps, Black and Hispanic students are also much less likely than White students to be enrolled in 4-year colleges in general (Bozick & Lauff, 2007;Dalton, Ingels, & Fritch, 2015) and more-selective colleges in particular (Bowen & Bok, 1998;Hearn 1991;Reardon et al, 2012). Longitudinal studies of admission to "very competitive" 4-year colleges have shown increasing underrepresentation of minority students (Alon & Tienda, 2007;Engberg, 2012;Karen, 2002;Posselt, et al, 2012). We aim to add to this literature by measuring gaps in a way that is sensitive to all college types and levels simultaneously.…”
Section: Improving On Prior Higher Education Student Stratification Rmentioning
confidence: 99%
“…We regularly observe, for example, that access to selective colleges does not appear equal between groupsminority and low-income students attend selective colleges at disproportionately low rates (Alon & Tienda, 2007;Astin & Oseguera, 2004;Bowen & Bok, 1998;Engberg, 2012;Posselt, Jaquette, Bielby, & Bastedo, 2012;Reardon, Baker, & Klasik, 2012). However, these findings do not help us understand the overall distribution of minority and low-income students in American higher education.…”
mentioning
confidence: 99%
“…Among the most difficult challenges we face as a society is social inequality, for which our postsecondary education system acts at once as the problem, by propagating disadvantages through disparate access to opportunities, and the solution, by serving as the key mechanism for social mobility. Countervailing trends are apparent in the steady growth over the past three decades in postsecondary participation rates among students from all backgrounds and in the increasingly competitive process of gaining admission to college-specifically to selective colleges-which favors students from higher socioeconomic backgrounds (Alon 2009;Engberg 2012;Hoxby 2009).…”
mentioning
confidence: 99%
“…It is well documented that students from higher socioeconomic status (SES) families are more likely to attend college, and to attend more selective institutions (Engberg 2012;Grodsky and Jackson 2009;Karen 2002;Paulsen and St. John 2002).…”
mentioning
confidence: 99%